EEG Phase Synchronization in Persons With Depression Subjected to Transcranial Magnetic Stimulation - Zuchowicz, Urszula; Wozniak-Kwasniewska, Agata; Szekely, David; Olejarczyk, Elzbieta; David, Olivier (Frontiers in Neuroscience, 2019)
Aim: The main objective of this work was to study the impact of repetitive Transcranial Magnetic Stimulation (rTMS) treatment on brain activity in 8 patients with major depressive disorder (MDD) and 10 patients with bipolar disorder (BP). Changes due to rTMS stimulation of the left dorsolateral prefrontal cortex (DLPFC) were investigated considering separately responders and nonresponders to therapy in each of both groups. The aim of the research is to determine whether nonresponders differ from responders suffered from both diseases, as well as if any change occurred due to rTMS across consecutive rTMS sessions. Methods: The graph-theory-based connectivity analysis of nonlinearity measure of phase interdependencies – Phase Locking Value (PLV) – was examined from EEG data. The approximately 15-minute EEG recordings from each of participants were recorded before and after 1st, 10th and 20th session, respectively. PLV calculated from data was analyzed using principal graph theory indices (strength and degree) within five physiological frequency bands and in individual channels separately. The impact of rTMS on the EEG connectivity in every group of patients evaluated by PLV was assessed. Results: Each of four groups reacted differently to rTMS treatment. The strength and degree of PLV increased in gamma band in both groups of responders. Moreover, an increase of indices in beta band for BP-responders was observed. While, in MDD-nonresponders the indices decreased in gamma band and increased in beta band. Moreover, the index strength was lower in alpha band for BP- nonresponders. The rTMS stimulation caused topographically specific changes, i.e. the increase of the activity in the left DLPFC as well as in other brain regions such as right parieto-occipital areas. Conclusions: The analysis of PLV allowed for evaluation of the rTMS impact on the EEG activity in each group of patients. The changes of PLV under stimulation might be a good indicator of response to depression treatment permitting to improve the effectiveness of therapy.